Diagnosis of alveolar and root fractures: an in vitro study comparing CBCT imaging with periapical radiographs - Solange KOBAYASHI-VELASCO; Fernanda Cristina Sales SALINEIRO; Ivan Onone GIALAIN; Marcelo Gusmão Paraiso CAVALCANTI
Abstract Objective To compare periapical radiograph (PR) and cone-beam computed tomography (CBCT) in the diagnosis of alveolar and root fractures. Material and Methods Sixty incisor teeth (20 higid and 40 with root fracture) from dogs were inserted in 60 anterior alveolar sockets (40 higid and 20 with alveolar fracture) of 15 macerated canine maxillae. Each fractured socket had a root fractured tooth inserted in it. Afterwards, each maxilla was submitted to PR in two different vertical angulation incidences, and to CBCT imaging with a small field of view (FOV) and high-definition protocol. Images were randomized and posteriorly analyzed by two oral and maxillofacial radiologists two times, with a two-week interval between observations. Results Sensitivity and specificity values were good for root fractures for PR and CBCT. For alveolar fractures, sensitivity ranged from 0.10 to 0.90 for PR and from 0.50 to 0.65 for CBCT. Specificity for alveolar fractures showed lower results than for root fractures for PR and CBCT. Areas under the ROC curve showed good results for both PR and CBCT for root fractures. However, results were fair for both PR and CBCT for alveolar fractures. When submitted to repeated measures ANOVA tests, there was a statistically significant difference between PR and CBCT for root fractures. Root fracture intraobserver agreement ranged from 0.90 to 0.93, and alveolar fracture intraobserver agreement ranged from 0.30 to 0.57. Interobserver agreement results were substantial for root fractures and poor/fair for alveolar fractures (0.11 for PR and 0.30 for CBCT). Conclusion Periapical radiograph with two different vertical angulations may be considered an accurate method to detect root fractures. However, PR showed poorer results than CBCT for the diagnosis of alveolar fractures. When no fractures are diagnosed in PR and the patient describes pain symptoms, the subsequent exam of choice is CBCT.